Clinical predictors of mechanical ventilation in Fisher/Guillain–Barré overlap syndrome. Issue 1 (23rd October 2008) - Funakoshi, K; Kuwabara, S; Odaka, M; Hirata, K; Yuki, N
Abstract : Background: Some patients with Fisher syndrome (FS) developed subsequent descending tetraparesis (Fisher/Guillain–Barré overlapping syndrome: FS/GBS). The assumption is that such descending progression may frequently lead to respiratory failure. Objective: To investigate whether patients with FS/GBS more often require artificial ventilation than those with typical GBS and which clinical and serological findings are useful predictors. Methods: Medical records were reviewed of patients who had acute ophthalmoplegia, ataxia and areflexia, as well as subsequent tetraparesis with monophasic course. Forty-five patients fulfilled the FS/GBS criteria. Clinical and serological features were analysed, and clinical predictors of mechanical ventilation were investigated. Results: FS/GBS patients more frequently required mechanical ventilation than did GBS patients (24% vs 10%, p = 0.04). The former also needed artificial ventilation earlier than the latter (p = 0.03), but none of the FS patients required it. As the initial symptom, ventilated FS/GBS patients more frequently showed titubation than non-ventilated patients (55% vs 18%, p = 0.04). During the course of the illness, descending tetraparesis was more common in 11 ventilated FS/GBS patients than in the other 34 non-ventilated patients (64% vs 21%, p = 0.02). The need for artificial ventilation was not associated with anti-GQ1b IgG antibodies, monospecific anti-GT1a IgG antibodies or IgG antibodies to various ganglioside complexes. Conclusions: FS/GBS patients significantly needed mechanical ventilation more often. Such patients showing titubation and descending tetraparesis need to be carefully monitored as the illness progresses because those clinical features are helpful predictors of respiratory failure.